The effectiveness of health-recreating programme of rock-climbing activities for 9-year-old children with attention deficit hyperactivity disorders - Kadiyeva, Margaryta; Blagii, Oleksandra (Quality in Sport, 2021)
The results of theoretical generalization and practical solution of the issue regarding increase of the effectiveness of health-recreating activities for children of primary school age with attention deficit hyperactivity disorders are described in this article. The objective of the study was to evaluate the effectiveness of the health-recreating activities programme for children of 9 to 10 years of age attention deficit hyperactivity disorders, using rock climbing. Methods and organization of the study. The following methods were used: theoretical analysis of special scientific and methodological literature; anthropometric and pedagogical techniques; and the methods of mathematical statistics. Children of the primary school age (9-year-olds, 26 children in total) took part in this study. Duration of the programme – 9 months. In each group, the activities were held 3 times a week, lasting 60 minutes. Among other methods, apart from rock climbing, were used the series of playing activities on the rock-climbing wall: relay races, physical activities, quests, role-play games with plot. The Wilcoxon signed-rank test(W-test) was used for the qualitative analysis of statistical data and for identifying reliable changes. Results. At the end of pedagogical experiment, reliable changes (р<0,05; р<0,001) happened in indicators, which characterized total body size. Positive influence of rock climbing was reflected in decrease of overweight children. Probable changes (р<0.001) appeared in indicators, which characterized the work of cardiovascular and respiratory systems. Under the influence of recreating rock-climbing activities for the children of primary school age (9-year-olds) reliable changes happened (р<0.001) in indicators, which characterized strength, flexibility and agility. Significant positive changes determined in indicators, which reflected the level of physical health and physical preparedness.